2017
DOI: 10.1177/0961203317700484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ACR and SLICC classification criteria in juvenile-onset systemic lupus erythematosus: a longitudinal analysis

Abstract: Objectives The Systemic Lupus International Collaborating Clinics (SLICC) group proposed revised classification criteria for systemic lupus erythematosus (SLICC-2012 criteria). This study aimed to compare these criteria with the well-established American College of Rheumatology classification criteria (ACR-1997 criteria) in a national cohort of juvenile-onset systemic lupus erythematosus (JSLE) patients and evaluate how patients' classification criteria evolved over time. Methods Data from patients in the UK J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 11 publications
4
25
0
6
Order By: Relevance
“…Specificity was not significantly different [19]. The UK juvenile SLE cohort evaluated only sensitivity, and SLICC also were more sensitive than ACR 1997, both at diagnosis (92.9% versus 84.1%, p < 0.001) and at last visit (100% versus 92%, p < 0.001) [20].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Specificity was not significantly different [19]. The UK juvenile SLE cohort evaluated only sensitivity, and SLICC also were more sensitive than ACR 1997, both at diagnosis (92.9% versus 84.1%, p < 0.001) and at last visit (100% versus 92%, p < 0.001) [20].…”
Section: Discussionmentioning
confidence: 84%
“…Few studies have evaluated the performance of different SLE classification criteria in cSLE, showing variables results. For cSLE, three studies demonstrated that SLICC criteria classify patients earlier than ACR 1997 [18][19][20]. In the multicentre European study by Sag and colleagues, the sensitivity of SLICC was higher (98.7% versus 85.3%, p < 0.001) but specificity was lower (76.6% versus 93.4%, p < 0.001) compared to ACR 1997, at time of diagnosis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other validation studies similarly showed a higher sensitivity and lower specificity of the SLICC compared with the ACR classification, although none of them elaborated on the stand-alone renal criterion. 11,[29][30][31][32][33] Only Ungprasert et al 33 identified 3 patients with SLE among 55 who met SLICC criteria that were classified based on the stand-alone criterion without commenting on their biopsy findings. We conclude that the SLICC classification may perform well as classification and conceivably also as diagnostic criteria for patients with renal biopsy findings consistent with LN, but we suggest reevaluation of the stand-alone renal criterion for clinical and research purposes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been only 2 studies comparing the sensitivity and specificity of ACR and SLICC criteria in cSLE 6,7 . More recently, there has been a larger study examining only the sensitivity of the 2 classification criteria 8 . The aim of our study was to determine and compare the sensitivities of ACR and SLICC criteria in cSLE within a large, multiethnic, single-center cohort.…”
mentioning
confidence: 99%